Advances in agronomy. - Sparks, Donald L., 1953- (Advances in Agronomy., 2002)
Advances in Agronomy has the highest impact factor among serial publications in Agriculture. The Science Citation Index, 1986, reports an impact factor over 2,459 and a cited half-life over 10 years. Volume 76 contains five excellent reviews on topics of great interest to crop and soil scientists as well as others in various fields. Chapter 1 is concerned with the potential of tropical soils to sequester carbon. Topics that are covered include soil inorganic and organic pools and dynamics, loss of soil organic pools from tropical soils, and potential for C sequestration in tropical soils. C.